(untitled) (Medical Forum Monthly, 2023)
Objective: To investigate the standards of personal hygiene in secondary level students. Study Design: Observational / descriptive / cross sectional study Place and duration of study: This study was conducted at Government Sardar Essa Khan Girls High School, Quetta from July 2014 to December 2014. Materials and Methods: The study was conducted on grade 7th & 8th students of Government Girls High School Quetta with the help of questionnaire. Health status of students was also examined by performing physical examination. Results: Amongst the target population 40.31% students were 11 to 13 years old, 57.65% were 13-16 years old while 2.04% students belonged to the 16.1 to 19 age group. Parents of the majority of the participants were literate. Family income of 52.65% students was above Rs. 15000/month. All the students had closed sewage system and community water supply in their houses. More than 80% of students were found neat, clean and healthy according to the criteria of health score designed for this study. Conclusion: This study indicates satisfactory personal hygienic conditions amongst target students but still there was a room for improvement. However, awareness campaigns should be conducted in schools to increase understanding about good hygiene practices.